ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESELAMATAN PENGOPERASIAN ALAT ANGKAT BONGKAR MUAT PETI KEMAS (Studi Kasus di PT. Pelabuhan Tanjung Priok) - Putri Sarah Alvernia; Bina Kurniawan; Daru Lestantyo (Jurnal Kesehatan Masyarakat (Undip), 2018)
Port is a workplace that has a high accident risk, one of them for loading and unloading activities by using lifting equipment. PT.Pelabuhan Tanjung Priok is a company engaged in the service of port services for container loading and unloading activities. These activities use lifting equipment that is Gantry Luffing Crane (GLC) and Overhead Crane (OHC) operated by the operator. This study aimed to analyze the factors that affected the safety of the operation of container loading and unloading equipment. In this research, the design used descriptive with qualitative analysis approach. The subject of research was 13 people consist of 8 main informants and 5 informant triangulation. The results of this study indicated that the level of education, working period and age had been in accordance with the rules set by the government, the level of education, employment and the higher age did not guarantee the operator would behave safely, but the operator's knowledge of safe working behavior was good enough, the attitude of the lift operator indicated that there were still operators who were not behaving safely, the state of the lifting machine was good because there has been checking every day, all operators have attended the training to get the SIO / K3 license, safety briefing done every shift change but only in the direction, the operating SOP already exists but the socialization has not been comprehensive throughout the operator, the assistant operators were very helpful operators in the operation of the tool, and the existence of punishment motivated operators to behave safely, but if there was a reward would be more motivate the operator to behave safely. The company should re-socialize the Operating Procedure SOP to all operators, conducted a two-way safety briefing and gave rewards as a form of appreciation to the operator.